Konsep Pendidikan Seumur Hidup Dalam Adab Belajar Siswa di SMP N 28 Palembang - hasrul, Hasrul Muhibbin; Ni’matus zuhroh (Jurnal Al-Hikam, 2024)
Related to the concept of courtesy in learning which is a guide for a student. The concept of continuing education is an effort to empower, develop and humanize humans. The courtesy values ​​contained in the book of Ta'lim al-Muta'llim in the student's learning path are not only related to horizontal relationships (God), but also to vertical relationships